Adubo orgânico enriquecido com conchas de ostras na produção do coentro: uma alternativa para o aproveitamento dos resíduos da malacocultura no nordeste paraense - MIRANDA, Beatriz da Silva (2018)
In the State of Pará, ostreiculture has been practiced in rural communities, mainly in the northeast mesoregion, resulting in high quantities of shells with inadequate management, promoting environmental pollution. However, in the composition of the oyster shells they contain high concentrations of Calcium and Magnesium and other nutrients in the organic form, allowing their use when associated with organic fertilizers. The present research aimed to use residual oyster shells, as an alternative source of calcium, magnesium, and other nutrients, in the enrichment of organic compound for use in organic vegetable production system, as an alternative in the proper management of solid oyster farming residues, Northeast of Paraense. The research was conducted in a greenhouse at the IFPA - Campus Castanhal Horticulture Sector, in Castanhal - PA, Brazil, in a randomized block design, with 5 treatments, 5 replicates in 25 plots. The "Verdão" coriander was cultivated in polyethylene pots of 6 kg, with the following treatments in the composition of the substrates: 1-superficial soil; 2-soil + organic compost + 3% oyster shells; 3-soil + organic compost + 6% oyster shells; 4-soil + organic compost + 9% oyster shells; and 5-soil + organic compound + 12% oyster shells. The soil surface was collected at a depth of 0.2 m, classified as a dystrophic Yellow Latosol, with low fertility, with 15.9% of saturation per base. The concentration of the organic compound in the substrate was 5 kg m2 (Cavalcante, 2015), obtained by aerobic composting in the proportion of 70% of vegetal residues (several leaves) and 30% of cassava scrapings, adding the percentages of 3%, 6%, 9% and 12% of dried and crushed oyster shells. The height (AP) and number of leaves per plant (NF) were evaluated in the coriander plant growth, and the yield, by green biomass (BV) and dry matter (BS), at 30 days of germination, and the quality of the substrates after cultivation, by the attributes (pH, Organic Matte - MO, Phosphorus - P, Calcium - Ca, Magnesium - Mg, Aluminum - Al, and Base Saturation - V). Compared to the Witness (T1), significant effects were observed with higher efficiency, from T3 (soil + organic compost + 6% oyster shells), which promoted, on average, higher performances in AP (20.64 cm) in the NF (general mean of 6.25 did not differ), in BV (4,950.26 kg ha-1) and BS (606,20 kg ha-1). In the qualitative attributes of the substrates, the greatest efficiencies were from T2 (soil + organic compost + 3% oyster shells), an adequate level to raise the V index to 88.78%, compared to the control (15.91%), attributed to elevation of pH (from 4.9 to 6.75), MO (from 14.4 to 23.9 g kg-1), Ca (from 0.3 to 5.65 cmolc dm-3), from Mg (from 0.2 to 1.65 cmolc dm-3), from P (from 6.0 to 155.55 mg dm-3), and reduction of Al (from 1.0 cmolcdm-3 to 0).Based on the results, it was concluded that the organic compound produced by composting with vegetable residues, of cassava scrapings and oyster shells from the 3% concentration promoted the improvement of substrate quality for coriander and other healthy vegetables, in organic production system under the environmental conditions of the present study.